Risk assessment of postoperative pneumonia in children with neurologic disorders and obesity. Issue 2 (28th November 2022) - Owusu‐Bediako, Kwaku; Mpody, Christian; Iobst, Christopher; Tobias, Joseph D.; Nafiu, Olubukola O.
Abstract: Introduction: Postoperative pneumonia increases the risk of postsurgical mortality, making it a serious healthcare‐associated complication. Children with preoperative neuromuscular impairments have a higher risk of postoperative pneumonia. Obesity is also a risk factor for postoperative pulmonary complications, including pneumonia. Moreover, obesity is increasingly prevalent among children living with a neurological diagnosis. Whether obesity increases the risk of postoperative pneumonia among children with neurologic diseases remains largely unknown. Therefore, we assessed the risk of postoperative pneumonia among children with neurologic diagnoses based on their obesity status. Methods: We analyzed a retrospective cohort of children ≤18 years from the National Surgical Quality Improvement Program (2012–2019) database who underwent inpatient orthopedic surgery. We used Cox proportional regression model to estimate the hazard ratio for the association between neurologic disorders and postoperative pneumonia. In addition, we included an interaction term between body mass index and neurologic disorders to evaluate the moderating effect of obesity status and then performed stratified analyses to compare the magnitude of hazard ratios across body mass index subgroups. Results: A total of 60 745 children underwent inpatient orthopedic surgery during the study period, of whom 43.6% were healthy weight and 30.8% overweight/obese. The median age was 13 years (Interquartile range: 8–15). The incidence of postoperative pneumonia was higher among healthy weight patients with neurologic disorders than healthy weight patients without any neurologic disorders [Hazard ratio: 3.55 vs. 0.34]. Furthermore, the association between neurologic disorders and postoperative pneumonia was strongest among overweight patients than healthy weight or obese patients [Hazard ratio:11.88 vs. 9.45 vs. 4.40]. This observation was consistent across the various neurologic disorders analyzed. Conclusion: Childhood obesity buffered the association between neurologic disorders and postoperative pneumonia, consistent with an 'obesity paradox'. Further research exploring the underlying mechanisms for the obesity paradox in children with neurologic disorders is warranted.